Guidelines on acute gastroenteritis in children: a critical appraisal of their quality and applicability in primary care - van den Berg, José (BioMed Central, 2011)
BACKGROUND: Reasons for poor guideline adherence in acute gastroenteritis (AGE) in children in high-income countries are unclear, but may be due to inconsistency between guideline recommendations, lack of evidence, and lack of generalizability of the recommendations to general practice. The aim of this study was to assess the quality of international guidelines on AGE in children and investigate the generalizability of the recommendations to general practice. METHODS: Guidelines were retrieved from websites of professional medical organisations and websites of institutes involved in guideline development. In addition, a systematic search of the literature was performed. Articles were selected if they were a guideline, consensus statement or care protocol. RESULTS: Eight guidelines met the inclusion criteria, the quality of the guidelines varied. 242 recommendations on diagnosis and management were found, of which 138 (57%) were based on evidence. There is a large variety in the classification of symptoms to different categories of dehydration. No signs are generalizable to general practice. It is consistently recommended to use hypo-osmolar ORS, however, the recommendations on ORS-dosage are not evidence based and are inconsistent. One of 14 evidence based recommendations on therapy of AGE is based on outpatient research and is therefore generalizable to general practice. CONCLUSIONS: The present study shows considerable variation in the quality of guidelines on AGE in children, as well as inconsistencies between the recommendations. It remains unclear how to asses the extent of dehydration and determine the preferred treatment or referral of a young child with AGE presenting in general practice.